Penerapan Data Mining Pada Analisa Pola Pembelian Obat Menerapkan Algoritma Hash Based - Aldisa, Rima Tamara (Forum Kerjasama Pendidikan Tinggi, 2023)
Along with the times, human life is also developing. Both from the mindset, perspective and way of life. The development of the times requires society to participate in developing following an increasingly sophisticated era. One of the developments that cannot be denied in social life is the development of increasingly sophisticated technology. So that in doing a business skills are needed in managing and managing a business in accordance with technological developments. The business of selling drugs or often called pharmacies is a business that is spread in almost all corners of the world, including in Indonesia. Pharmacy is a business engaged in medicine. Pharmacies sell various types of drugs that are likely to be prescribed by a medical doctor, or other drugs that are commonly purchased by the public. Here the author's case study is one of the pharmacies in the East Jakarta area. The sustainability of a business can be influenced by several aspects, but the main aspect that is very influential is business management. The database is information about all transactions that have been carried out in the business. Where with the previous sales database, business owners can assess which products are of great interest to consumers and which are not of interest to consumers. This can help business owners prevent losses in terms of expiration dates and manage stocks of goods. This management should be done by optimizing data mining by applying a hash-based algorithm. The Hash Based Algorithm is an algorithm that aims to find combination patterns of several alternatives with criteria or attributes that are used as comparisons by calculating using filtering techniques so as to produce an itemset combination pattern. Based on the results of research using a hash based algorithm, 3 itemsets were produced which became the top priority, namely B = Amoxiline, E = Amyl Nitrite and G = Biotin with a support value of 20% and 50% confidence